Analysis Of Accounts Receivable and Its Impact on The Going Concern Of Cu Bina Kasih Pematangsiantar (Period 2022–2024) - Nurfika Dwi Putri; Djuli Sjafei Purba; Wico J Tarigan (Jurnal Ilmiah Accusi, 2026)
This study examines the management of accounts receivable and its implications for the going concern of CU Bina Kasih Pematangsiantar during the 2022–2024 period. Accounts receivable constitute the principal productive asset in savings and loan cooperatives because they arise directly from member lending activities and serve as a major source of institutional income. Accordingly, the quality of receivables management is closely associated with liquidity, cash flow, profitability, and the long-term continuity of cooperative operations. This study adopted a qualitative descriptive design. Data were obtained through interviews, observation, and documentation, and were analyzed using data reduction, thematic organization, and interpretive conclusion drawing. The findings indicate that receivables management at CU Bina Kasih had been implemented through credit approval, recording, monitoring, and collection procedures; however, its overall effectiveness remained limited. The cooperative continued to face problematic receivables, a moderate NPL ratio, and weak profitability throughout the study period. The findings also show that problematic receivables were influenced by both internal factors, including weaknesses in credit assessment and monitoring, and external factors, including members’ post-pandemic economic constraints. Most importantly, the study demonstrates that receivables quality had a direct impact on the cooperative’s going concern through its effects on liquidity, productive asset quality, and earnings capacity. The study concludes that sustainable cooperative operations depend not merely on the expansion of lending activity, but on the collectability, governance, and risk profile of the receivables portfolio